Estimating the Permeability of the Ceramic Coating on Lithium-Ion Battery Separators via the Ideal Laminate Theory - Mun, Sung Cik; Won, Jong Ho (Frontiers in Energy Research, 2022)
In this study, a simple method for quantifying the porous nature based on the permeability of the thin ceramic coating on microporous polyolefin flims used as separators in lithium-ion batteries is demonstrated. The air permeability of the ceramic coating was determined via the ideal laminate theory (ILT), which is widely accepted for multilayered films or well-defined laminates. This study mainly aims at introducing an ILT-based resistors-in-series model with the Gurley method and its potential applications in battery separators. We investigated a few previously reported examples of ceramic-coated separators to compare the air permeability of various ceramic coatings along with their base polyolefin films.